Analisis Website Promosi di Banyan Tree Bintan Resort - Jihan Aulia Fatin; Trisna Putra (Universitas Katolik Widya Karya Malang, 2023)
Website promotion is a process of increasing visibility, traffic, and online presence which is a way to find and attract potential visitors by listing the website on popular internet directions using Search Engine Optimization and Search Engine Submission. With a more in-depth analysis of the quality of service on the website through the End User Computing Satisfaction (EUCS) method, Banyan Tree Bintan can take more targeted corrective actions to improve interactions with guests, increase guest satisfaction levels, and optimize the communication and interaction goals to be achieved through the website. This research is a descriptive research with Content Analysis approach. This study used a sampling total technique. Data collection was carried out in July 2023. The purpose of this research is to analyze the Banyan Tree Bintan promotional website using the End User Computing Satisfaction (EUCS) method from the aspects of content, accuracy, format, ease of use, and timeliness. The results of this study indicate that the Banyan Tree Bintan website is quite good and does not experience any problems. However, in terms of timeliness, it needs improvement regarding response time and also quick responses.